A Virtual Machine Placement Algorithm for Resource Allocation in Cloud-Based Environments - Lima, David H. S.; Aquino, Andre L. L.; Curado, Marilia (Anais do Workshop de Gerência e Operação de Redes e Serviços (WGRS); 2023: Anais do XXVIII Workshop de Gerência e Operação de Redes e Serviços, 2023)
This research paper presents a Virtual Machine Placement algorithm designed to optimize the service allocation process, which is one of the most significant challenges in resource allocation and management. Our solution employs a ranking strategy based on global resource scarcity, where we consider all the information contained in datacenter hosts during the allocation process. We compare our approach with two different literature-based methods regarding task allocation time and the number of allocated resources. To evaluate our proposal, we consider scenarios in which requisitions arrive at different times or simultaneously. The first scenario represents a realistic situation where no knowledge is available regarding task arrival. Meanwhile, the second scenario represents a dense situation where many tasks arrive together. Our evaluations show that our solution yields better results in both cases, especially when requisitions arrive simultaneously. Our solution reduced the allocation time by around 25% on average and achieved better load distribution among hosts.